Discovery of ontologies from implicit user knowledge - Haller, David; Lenz, Richard (CEUR Workshop Proceedings, 2020)
The purpose of the Semantic Web is to enable worldwide access to humanity's knowledge in a machine-processable way. A major obstacle to this has been that knowledge is often either represented in an incoherent way, or not externalized at all and only present in people's minds. Populating a knowledge graph and manually building an ontology by a domain expert is tedious work, requiring great initial effort until the result can be used. As a consequence, knowledge will often never be made available to the Semantic Web. The aim of this project is to develop a new approach for building ontologies from implicit user knowledge that is already present, but hidden in various artifacts like SQL query logs or application usage patterns.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Data Integration; Knowledge Graph; Query-Driven; Schema Inference; Semantic Web